Improving the tribological and anti-corrosion property of the WS2 film through Ta doping. (October 2021) - Yang, Jun; Wang, Desheng; Fu, Yanlong; Wang, Qinqin; Hu, Ming; Jiang, Dong; Gao, Xiaoming; Sun, Jiayi; Weng, Lijun
Abstract: The easy oxidation and poor corrosion resistance of the sputtered WS2 film would limit its application in spacecraft due to the sharp deterioration of lubricity resulting from the contact with the marine atmosphere inevitably with the increasing space launch from sea or seaside. In this study, the active metal Ta was skillfully introduced into the WS2 film through co-sputtering of the WS2 and Ta targets. The influence of the doped Ta related microstructure regulation on the tribological and anti-corrosion properties of the prepared composite films was investigated. It showed that the incorporation of the active Ta would activate the residual O atoms to form Ta2 O5 phase while making the WS2 phase partly oxidized to form the WSx Oy and WO3 . WS2 –Ta composite films with low Ta content exhibited low friction coefficient and long wear life more than 3 times of that for pure WS2 film. In addition, the corrosion resistance of WS2 –Ta film was improved by a positive shift of corrosion potential in salt spray with increasing the Ta content, originating from the passivation effect of the Ta2 O5 phase and the WSx Oy phase in the film as well as the dense structure. Highlights: WS2 –Ta composite films with different Ta contents were prepared by magnetron sputtering system. The incorporation of the much active Ta would activate the residual O atoms to form the Ta2 O5 and partly WSx Oy. phase. WS2 –Ta composite film exhibited significantly improved tribological property and corrosion resistance.